Evaluating the performance efficiency of Iraqi Islamic banks: an applied study compared with Emirati banks for the period (2005-2014) - حيدر يونس الموسوي; آمنة صبري (Iraqi Journal for Administrative Sciences, 2024)
Expresses as banks, the backbone of the economy, his aorta, engine basis, and with the financial markets play a pivotal role in the financing of the rest of the economic sectors and effectiveness within the domestic economy. The simulation of the religion of Islam and consistent with the principles of the Chairperson had emerged from Islamic banks to fine-tune in content and details with the teachings of the religion in the area of finance and investment banking system and supporting the economy .Islamic banks are institutions to abide by all its work in accordance with the provisions of the Islamic Shariah and feature from the rest of the types of banks and multiple areas of funding or investment wording and does not deal with credit, limits the legitimate sales. Has widened the role of this type of banks in the economy is not at the level of the Islamic countries but extended to many Western countries, launched the Global banks develop branches of the Islamic Banking. Now the Islamic banks rich scope and a center to attract many intellectuals and investors in the field of the financial and banking specifically, especially after its crises of the financial system in all its forms the latest global financial crisis (2007-2008). The aim of this study to many of objectives, the most important of which is the evaluation of the efficiency performance of Islamic banks Iraq as a new experience in the financial arena Iraqi economic, assessing the efficiency and performance of some Islamic banks in the United Arab Emirates. Add to this the in-depth analysis of some of the performance indicators of the Chairperson and the measurement of their content, the study proceeds from the Major assumption the summarized the weakness of the efficiency of the performance of the banks and the Iraqi Islamic compared with their counterparts in the UAE, which emanate hypotheses multiple subnets.